Andrographis paniculata Leaves Extract Inhibit TNF-α and Caspase-3 Expression of Septic Rats’ Intestinal Tissues - Ardika, Ryco Giftyan; Budiono, Bernardus Parish; Widiastiti, Nyoman Suci; Maharani, Nani; Susilaningsih, Neni; Sandra, Ferry (The Indonesian Biomedical Journal, 2024)
BACKGROUND: Microcirculation and cellular disturbances caused by sepsis might trigger significant intestinal damage. Andrographis paniculata extract decreases inflammatory intestinal epithelial cells with its role as an antiparasitic and anti-inflammatory agent. However, A. paniculata extract’s effect on sepsis have not been commonly studied, especially in the intestinal tissues. Therefore, this study was conducted to determine A. paniculata leaves extract (APLE) effect in sepsis-induced intestinal tissues of rats by examining the expression of inflammatory cytokines involved in sepsis, namely tumor necrosis factor (TNF)-α and Caspase-3.METHODS: Rats were divided into five groups; two groups received no pretreatment and the other three groups received 200, 400, and 500 mg/kg BW/day APLE, respectively. Three pretreated groups and one group with no pretreatment were then injected with 1 mg/200 g BW lipopolysaccharides (LPS) intraperitoneally to create septic rat models. Three days after the LPS-induction, rats were euthanized and the expression of TNF-α and Caspase-3 were assessed based on the immunohistochemical staining of rats’ intestinal tissues.RESULTS: Compared with NaCl (sham), LPS significantly (p<0.001) induced TNF-α expression from 6.60±1.36 to 25.37±1.74. Pretreatment of 200, 400, and 500 mg/kg BW/day APLE could significantly (p<0.001) inhibit the LPS-induced TNF-α expression (18.82±1.36, 11.45±1.18, and 6.89±1.90, respectively). Similar with TNF-α, compared with NaCl (sham), LPS significantly (p<0.001) induced Caspase-3 expression from 6.92±1.66 to 23.59±2.25. Pretreatment of 200, 400, and 500 mg/kg BW/day APLE could significantly (p<0.001) inhibit the LPS-induced Caspase-3 expression (17.47±1.68, 12.99±1.51, and 5.59±1.51, respectively).CONCLUSION: The pretreatment of APLE could inhibit the LPS-induced TNF-α and Caspase-3 expression, therefore APLE could be suggested as a potential sepsis-preventing agent.KEYWORDS: Andrographis paniculata, sepsis, TNF-α, Caspase-3, lipopolysaccharide